Life in Miniature Exhibition at the Kelsey Museum of Archaeology: Intertwining Theoretical and Traditional Approaches in the Exhibition of Terracotta Figurines and Other Miniature Objects - Stephanie M. Langin-Hooper (Les Carnets de l’ACoSt)
The Kelsey Museum of Archaeology recently hosted a special exhibition, entitled Life in Miniature: Identity and Display at Ancient Seleucia-on-the-Tigris, co-curated by myself (Stephanie Langin-Hooper) and Sharon Herbert.Indeed, the focus of the show was to illustrate how and why terracotta figurines and other miniatures were used in the everyday lives of the people of Seleucia-on-the-Tigris.